Analysis of the Board of Directors' Leadership in Carrying Out Professional Business Transformation at PT Garam (Persero) - Budiyono, Budiyono; Sunarsi, Denok; Wahyudi, Wahyudi (INOVASI, 2025)
The purpose of this research is to know and descriptively analyze the leadership of the Board of Directors of PT Garam (Persero) in carrying out business transformation professionally. The method used in this research is qualitative research, where qualitative research aims to understand the phenomenon regarding what the research subject’s experience, such as behavior, perceptions, motivations, actions, holistically through descriptions in the form of words and language, in a specific natural context by using various scientific methods. The next stage is to deepen the data obtained through interviews with direct sources intensively. Then analyze the interview data obtained and compare it with supporting company documents. Through transformational leadership, the Board of Directors of PT Garam (Persero) for the period of 2022-2024 leads the Company with the goal of improving its performance over time. With the right managerial approach, the Board of Directors of PT Garam (Persero) is deemed capable of optimizing all human resources at PT Garam (Persero) to work efficiently, professionally, and beneficially. In addition, the leadership of the Board of Directors of PT Garam (Persero) for the period of 2022-2024 is considered capable of overcoming challenges in the Company in carrying out transformation towards a better direction in a sustainable manner)